Entanglements of dis:abilities and technologies in public space and life: insights from a mobile and visual methods study including video-based mobile eye-tracking - Bork-Hüffer, Tabea; Misera, Jan; Melchert, Johannes; Pykett, Jessica (Annals of the Association of American Geographers, 2025)
Technologies are often proposed as means to enhance accessibility, mobility, and autonomy for people with disabilities. This article critically examines such claims and aims to conceptualize and empirically explore the relational entanglements of disabilities and technologies in everyday life, highlighting how diverse technologies—intimate, assistive, and infrastructural—can simultaneously enable and constrain accessibility, autonomy, and inclusion. To this end, the article weaves together critical disability studies, digital geographies, and feminist science and technology studies, introducing the concept of dis:abilities to describe the relational, inseparable, fluid, and diverse nature of disabilities and abilities. It develops the notion of relational technological entanglements with dis:abilities and places this in dialogue with emerging scholarship that pursues innovative methodological and empirical approaches to explore entanglements. The article presents findings from a co-productive, mobile and visual research study with disabled people, including video-based mobile eye-tracking. Findings reveal that although technologies play a central role in enabling everyday practices, mobilities, autonomy, and emotional well-being, the participants’ narratives underscore the fragilities, ambiguities, and nonlinearities of relying on a range of technologies. Technological temporalities and ephemeralities can give rise to moments of vulnerability. Moreover, the benefits these technologies offer often come at the cost of significant effort, time, and financial resources. Despite being framed as offering seamless support, their material and visible dimensions can reinforce exclusion, discrimination, and alienation within the dis/ability complex.
Published online: 13. August 2025
Gesehen am 22.08.2025